Bacharéis em música formados pela UFPB e suas concepções pedagógicas como professores de instrumento. - Ribeiro, Luíza Limeira Rosas (2021)
This paper presents a research that aims to understand the perception of bachelors in relation to their own pedagogical practices. The life history methodology was adopted, using narrative and semi-structured interviews, having collected data with six graduates of the Bachelor's of Music at the Federal University of Paraíba (UFPB). This work sought to characterize the Bachelor of Music course at UFPB and the intended training profile; then, to analyze the bachelor's conceptions about acting as a musician and as a teacher; finally, to analyze the difficulties encountered in their pedagogical performance. The analysis sought to relate the student's experiences with their graduation from higher education, observing the conceptions of music, the job market and the perceptions that the interviewees had about their own musical trajectories. However, the course is primarily focused on instrumental performance, without any concern with didactic preparation, although all participating graduates acted as instrument teachers. This generated a relationship of contradiction between their musical life experiences – pedagogical practices – and their training. We conclude that it is necessary to rethink the development of curricula in the undergraduate course, specifically the Bachelor of Music course at UFPB, because when there is a dialogue between the various learning processes of individuals, there can be a significant complement in pedagogical training.